Prevalence of Cleft Lip and Palate in the Developing Countries of Asia and Africa: A Review - Shrestha, Ashish; Hoang, Ha; Gardner, Sue; Pradhan, Archana; Crocombe, Leonard (Journal of Nepal Paediatric Society, 2022)
Introduction: The objective of this paper is to review the literature on the incidence of cleft lip and palate (CLP) in the developing countries of Asia and Africa. The existing literature tends to focus on developed countries and there is lack of research in developing countries. Methods: The studies that met the inclusion criteria were reviewed and data extracted. There were 20 studies done in Asian and African countries which were included. Results: The incidence of CLP in Asian countries is markedly greater than in African countries. Most studies report a male predominance in CLPs and a female predominance in cleft palates. The male dominance is seen more than other developing countries which is consistent with other Asian countries and the same has been found in African countries. In the Nepalese study, females were slightly more affected than males among all clefts. The incidence or prevalence in the frequency and types of malformations of CLP in developing countries has been provided. Conclusions: The review underlines the need for an aggressive approach to prevent and control CLP in patients in developing countries.